A ciência no espaço educacional da criança: do fazer ciência à ciência do fazer - Souza, Carolina Rodrigues de (Revista Eletrônica de Educação, 2016)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false PT-BR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Cambria; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-ansi-language:PT-BR;} --> <!--[endif] --> <!--StartFragment--><p class="MsoNormal" style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;"><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <p class="MsoNormal" style="text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;"><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} --> <!--[endif] --> DOI: http://dx.doi.org/10.14244/198271991449 Abstract<!--[if gte mso 9]> <![endif]--> This article aims to reflect on the possible articulations of the development of science in the education of children and their respective childhoods. While in Kindergarten and Elementary School students are, above all, children, and as such, subjects endowed with intelligence, emotions, and feelings. They are able to make observations, retain information, propose arguments, participate in discussions, and make choices that allow them to exercise free expression of theirs thoughts in many different languages. However, to ensure the effective participation of the child as a subject of today, not an intented being, it is necessary to reconsider the actions and relationships in the school environment. In this sense, this study highlights contributions on how the educational process of science can/should be thought in the process of children education. Also, we hope to provide access to scientific culture without detracting the childhoods. We highlight the possibility of using some powerful elements of science in the school environment to sharpen curiosity and improve new worldviews. Often different from the adult perspective, science in children education should emphasize issues such as the specificity of child logic, which encompasses creativity, imagination, fantasy, and desire. This article, in its theoretical nature, discusses notions such as childhood, children, and science in order to consider a type of early childhood education in which an educational routine with elements of scientific culture would enable the occurrence of childhood practice. Keywords: Children, Childhood, Science education. Resumo Este artigo objetiva refletir sobre as possíveis articulações do desenvolvimento das ciências na educação das crianças e suas respectivas infâncias e parte da compreensão de que na Educação Infantil e nos primeiros anos do Ensino Fundamental, os estudantes antes de alunos são crianças, e como tais, são sujeitos completos, dotados de inteligência, emoções e sentimentos; capazes de observar, registrar informações, argumentar, debater, fazer escolhas e expressar-se em diferentes linguagens. Para garantir a participação efetiva da criança como sujeito hoje, e não um “vir a ser,” é necessário rever as ações e as relações no seu espaço escolar. Este trabalho aponta formas de pensar o processo educativo das ciências na formação das crianças para possibilitar seu acesso à cultura científica, sem desvalorizar as infâncias. Sugere, igualmente, elementos da ciência no espaço escolar da criança como veículo de potência para aguçar a curiosidade e novos olhares para o mundo, dentro da lógica infantil, que engloba criação, imaginação, fantasia e desejo, muitas vezes diferente do olhar do adulto. De natureza teórica, o artigo trabalha noções tais como crianças, infâncias e ciências, no intuito de pensar uma educação cujas práticas educativas, com elementos da cultura científica, possibilitem o exercício da infância. Palavras-chave: Crianças. Infâncias. Educação em Ciências. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--EndFragment-->